Engagement in Online Learning: Student Attitudes and Behavior During COVID-19 - Hollister, Brooke; Nair, Praveen; Hill-Lindsay, Sloan; Chukoskie, Leanne (Frontiers in Education, 2022)
The COVID-19 pandemic resulted in nearly all universities switching courses to online formats. We surveyed the online learning experience of undergraduate students (n=187) at a large, public research institution in course structure, interpersonal interaction, and academic resources. Data was also collected from course evaluations. Students reported decreases in live lecture engagement and attendance, with 72 percent reporting that low engagement during lectures hurt their online learning experience. A majority of students reported that they struggled with staying connected to their peers and instructors and managing the pace of coursework. Many students also reported considering taking a gap in their education. Students had positive impressions, however, of their instructional staff. Majorities of students felt more comfortable asking and answering questions in online classes, suggesting that there might be features of learning online to which students are receptive, and may also benefit in-person classes.